Prevalence of Neonatal Sepsis and Associated Factors among Neonates in Neonatal Intensive Care Unit at Selected Governmental Hospitals in Shashemene Town, Oromia Regional State, Ethiopia, 2017 - Aytenew Getabelew; Mihret Aman; Endashaw Fantaye; Tomas Yeheyis (International Journal of Pediatrics)
Background. Neonatal sepsis is an important cause of morbidity and mortality among neonates in developing countries accounting for 30-50% of total deaths each year. Childhood mortality is often used as broad indicator of the social development or a specific indicator of health conditions of a country. Objectives. The objective of this study is to assess the prevalence of neonatal sepsis and associated factors among neonates admitted in neonatal intensive care unit at two hospitals in Shashemene town, Ethiopia. Method. An institution based cross-sectional study with retrospective document review method was conducted in NICUs of two governmental hospitals in Shashemene town. Sample size was calculated by using single population proportion sample formula and the final sample size was 244. The study subject was selected by using systematic random sampling method, and adopted data collection tool was used. Then the collected data was coded and entered in to SPSS for windows version 20.0 for cleaning, editing, and analysis. Binary and multiple logistic regressions have been used to observe the association between independent variables and dependent variable. Result. The overall prevalence of neonatal sepsis in this study was 77.9%. From this 65% and 35% of neonates developed early onset neonatal sepsis and late onset neonatal sepsis, respectively. This study found out that age of neonates, birth asphyxia, and use of oxygen via mask were significantly associated with neonatal sepsis. Conclusion and Recommendation. The most risk factors of neonatal sepsis were identified as age of neonates, birth asphyxia, and use of oxygen via mask strongly associated with prevalence of NS. Based on this results we recommend the concerned body to focus on the prevention of risk factors rather than treating the disease after it occurs.